Telemedicine after COVID: An unanticipated benefit to a pandemic (Journal of Pakistan Orthopaedic Association, 2020)
Healthcare providers have been featured prominently throughout the global response to COVID-19. Images of first responders, nurses, and ICU doctors became the symbols of courage for the rest of us to follow. The roles and expectations of those on the front line are clear and their job is well defined. For others, like orthopaedic surgeons, finding our place in all of this has been more confusing.            Trauma, infection, and cancer: these conditions do not stop because of a virus, but they account merely for a small subset of the whole of orthopaedic surgery. Orthopaedics by nature is a field designed to restore the health, temporarily lost, of the inherently well. Appropriately so, our patients were some of the first to have their procedures delayed, and our elective practices the least defendable to continue as the outbreak worsened.